Associations of lipoprotein subclasses and oxidative stress status in pulmonary and pulmonary plus extrapulmonary sarcoidosis - Ivanisevic, Jasmina; Vekic, Jelena; Zeljkovic, Aleksandra; Stefanovic, Aleksandra; Kotur-Stevuljevic, Jelena; Spasojevic-Kalimanovska, Vesna; Spasic, Slavica; Vucinic-Mihailovic, Violeta; Videnovic-Ivanov, Jelica; Jelic-Ivanovic, Zorana (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Background: Sarcoidosis is an inflammatory disease with pulmonary and extrapulmonary manifestations. In such pathologic conditions, increased oxidative stress and rearrangement of high-density lipoprotein (HDL) and low-density lipoprotein (LDL) may occur. Objective: This study evaluated association of oxidative stress and lipoprotein subclasses in severe forms of pulmonary and pulmonary plus extrapulmonary sarcoidosis. Methods: Lipid parameters, LDL and HDL subclass distributions, high-sensitivity C-reactive protein (hsCRP), serum amyloid A (SAA), paraoxonase 1 (PON1), malondialdehyde (MDA), total-oxidant status (TOS), sulfhydryl (SH) groups, pro-oxidant anti-oxidant balance (PAB) were determined in 77 patients (53 isolated pulmonary and 24 pulmonary plus extrapulmonary) and 139 controls. Results: Both pulmonary and extrapulmonary sarcoidosis patients had significantly higher levels of triglycerides and TOS (P